Super buddies [videorecording (DVD)] - Vince, Robert; Earles, Jason; Hanks, Colin, 1977-; Stoner, Alyson, 1993- (Disney DVD., 2013)
An ordinary day at Fernfield Farms turns extraordinary when Budderball, Mudbud, B-Dawg, Buddha and Rosebud discover mysterious rings that grant them each a unique super power. Before you can say, 'Buddies, assemble,' the pups unleash their amazing abilities and race to the rescue when a shape-shifting bully from outer space threatens the planet. But can they succeed in kicking major tail without revealing their new secret identities?